Service Delivery by Health Facilities in Papua New Guinea - World Bank (World Bank, Washington, DC, 2018)
Papua New Guinea (PNG) has seen some improvements in health indicators over the past 25 years, but the pace of improvements is not as robust as expected. A better understanding of service delivery is critical to help PNG achieve the goals set in the PNG National Health Plan (2011–2020) and accelerate improvements in health outcomes. In this context, a primary survey was conducted at all secondary (levels 5 and 6), tertiary (level 7), and a random selection of functional upper-primary-level health facilities (levels 3 and 4). The report analyzes whether primary and secondary health care facilities in PNG have an adequate level of resources, both human resources and other material inputs, to deliver quality health care services and to determine whether the inputs are combined in an efficient manner to produce health care services.